The Influence of Work Discipline and Career Development on Employee Performance Mediated by Job Satisfaction at the Kendari City PDAM Office Research Results - Nur, Muh.; Abdul, Muhammad Zul Ardiansyah; Tambunan, Rince (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
This study investigates the influence of work discipline and career development on job satisfaction and employee performance at the Kendari City PDAM Office, as well as the mediating role of job satisfaction. Using a quantitative approach with the Smart PLS application, data were collected from 72 employees. The results show that work discipline has a positive and significant effect on job satisfaction and employee performance. Career development also has a positive and significant impact on job satisfaction but shows a positive yet insignificant effect on employee performance. Furthermore, job satisfaction positively and significantly affects employee performance, confirming its critical role as a mediating variable. Specifically, job satisfaction mediates the influence of both work discipline and career development on employee performance, strengthening the overall impact of these factors. These findings highlight the importance of implementing strict yet fair work discipline policies to enhance satisfaction while aligning career development programs with employee expectations to sustain motivation and performance. Overall, this research underscores that job satisfaction serves as a vital mechanism linking human resource practices to improved performance outcomes in public sector organizations like the Kendari City PDAM Office.